The Propaganda of the Harness: On the Reasonable Voice of Reason - van Deventer, Vasi (PINS-Psychology in Society, 2026)
Anita Craig's call to live for a future is a warning. The entire article is governed by the fear of unknown circumstances, a possible danger lurking ahead. And against this background she delivers her message with conviction. The danger she speaks of is all too clear Our flirtation with unreasonable practices endangers our practical and theoretical prosperity. We may be heading for an impoverished future, which may not allow us to live well. We should learn to treasure reason and reasonableness, she says, because this and this alone would enable us to harness a future which would serve us well.